2014
DOI: 10.1016/j.sdj.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to tooth loss among the elderly: A cross sectional study

Abstract: It can be concluded that less education or increased clinical attachment level loss may increase number of missing teeth. Additionally, age may cause teeth loss in the presence of smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 30 publications
(37 reference statements)
3
36
1
7
Order By: Relevance
“…In the present study we found that more number of males had missing tooth and gum problems (81.2% and 68.3% respectively) as compared to females (74.5% and 63.9% respectively). The results are similar to other studies which have reported that periodontal problems and tooth loss was high in males [18-20]. These authors have reported that greater periodontal destruction in males is because of more calculus, periodontal pocket and association with smoking, and later leads to loss of teeth.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study we found that more number of males had missing tooth and gum problems (81.2% and 68.3% respectively) as compared to females (74.5% and 63.9% respectively). The results are similar to other studies which have reported that periodontal problems and tooth loss was high in males [18-20]. These authors have reported that greater periodontal destruction in males is because of more calculus, periodontal pocket and association with smoking, and later leads to loss of teeth.…”
Section: Discussionsupporting
confidence: 91%
“…Auch konnten in mehreren Studien bei Patienten mit mangelhaftem oraldentalen Funktionszustand und einem niedrigen Body-Mass-Index (BMI), eine geringere Albuminkonzentration im Serum sowie Defizite unterschiedlichster Mikronährstoffe gegenüber vergleichbaren bezahnten Patienten gefunden werdenim Mini Nutritional Assessment (MNA) wiesen diese Patienten auch häufig niedrige Scores auf und ernährten sich selektiv [7,9] Sozialstatus sinkt. Ein niedriger Bildungsstand ist positiv mit einer verminderten Anzahl von Zähnen im Alter korreliert [12,13].…”
Section: Zahnstatus Und Ernährungszustandunclassified
“…Prestige-based measures refer to individual's rank or status in a social hierarchy, typically evaluated with reference to people's access to and consumption of goods, services, and knowledge as linked to their occupational prestige, income, and education level" (8). In epidemiological studies, SEP is usually approached using variables such as education (9,10), occupation (11) and income (12). These measures appear to be strong predictors of oral health in numerous studies (13,14).…”
Section: Introductionmentioning
confidence: 99%